Food digital marketing on social media: trends and strategies of Brazil’s leading meal delivery app - Barros, Paloma Aparecida Anastacio; de Paula Matos, Juliana; Rodrigues, Michele Bittencourt; da Costa, Renata Júlia; Horta, Paula Martins (Frontiers in Nutrition, 2025)
ObjectiveTo analyze digital marketing trends of Brazil’s leading meal delivery application (MDA) company on Facebook (FB) and Instagram (IG) from 2011 to 2022.MethodsThis exploratory, longitudinal, and mixed-methods study examined a 10% sample of all posts published by this company during the study period. Posts were analyzed in terms of food categories, media and connectivity features, and advertising themes.ResultsThe company predominantly promoted unhealthy foods, frequently employing persuasive digital marketing strategies. While this pattern was consistent across both platforms, IG posts were more visually engaging and interactive, making greater use of brand elements, hashtags, conversations, emoticons, user interaction, and company tagging (all p < 0.001). In contrast, FB posts more commonly included external links. Twelve distinct advertising themes were identified. They reflected a broad and diverse range of marketing strategies, encompassing brand promotion, user engagement, contextual appeals, technological features, social responsibility, and other themes. IG posts more frequently featured themes such as entertainment and social interaction, consumption stimulus, application differentials, public figure endorsements, and social and corporate responsibility (all p < 0.05). Conversely, the theme of communication and news was more prevalent on FB. Longitudinal analysis revealed that the company adapted its content over time, refining its use of media tools and thematic strategies in response to evolving digital marketing.ConclusionThe company primarily advertised unhealthy foods on both social media, leveraging persuasive techniques and marketing strategies. These practices may hinder public health efforts to reduce the consumption of unhealthy foods.